Locke, Voltaire, Rousseau: Philosophical Genesis of Griboedov's Comedy “Woe from Wit” - V. A. Cherkasov; V. V. Demicheva; O. I. Eremenko (Научный диалог, 2025)
This article significantly expands the historical and philosophical perspective on Griboedov's views regarding the nature of human intellect. It delineates and substantiates the differences between the positions of the author of the comedy “Woe from Wit” and its protagonist Chatsky concerning tolerance for differing opinions as a criterion of human intellect. Sources of hidden quotations within Griboedov's text are identified through a method of “slow reading” of philosophical and literary works from the 17th and 18th centuries, such as John Locke's treatise “An Essay Concerning Human Understanding,” Voltaire's “Philosophical Letters,” and Jean-Jacques Rousseau's novel “Julie, or the New Eloise.” By employing an intertextual approach, the article clarifies Griboedov's ideological premises as the author of “Woe from Wit” within the broader context of European literature and philosophy from the 17th century to the early 19th century, as well as the socio-political climate in Russia on the eve of the December uprising. The authors conclude that Griboedov critiques, through artistic means, the Rousseau-inspired mindset of Chatsky, characterized by subjective limitations, ignorance of real people and life circumstances, aggressiveness detrimental to society (the “woe” experienced at the end of the comedy is not solely that of Chatsky), and a form of youthful maximalism — essentially, intolerance for opposing viewpoints. It is asserted that the catastrophic resolution of the comedy reflects the playwright's pessimistic outlook on the intellectual development of the Russian educated society.